Specificity in the physical preparation of elite rugby union football players - Gamble, P. (2005)
The present thesis explored various applications of training specificity with regard to elite-level rugby union football players of various ages. A novel approach to metabolic conditioning employing skill-based conditioning games was investigated with elite-level senior professional players, during the course of a preseason training period. Training responses were assessed using a submaximal intermittent shuttle test performed at weekly intervals. Significant differences post-training (p<0.01) were observed for %HRmax reached during the final test stage and recovery of HR from the end of the final stage to the end of the final 1-minute rest period. The second study examined effectiveness of a circuit format for strength training in elite senior professional players during a preseason training period. Following the circuit based strength training, deadlift and bench pull I-RM strength scores were significantly improved both in comparison to pre-tests (p<0.01) and end season scores (p<0.01). Bench press scores were also significantly improved following the training period (p<0.01), and post-test bench press scores were improved relative to end season scores, albeit to a lesser extent (p<0.05). An Olympic lift training intervention was undertaken with Junior academy-level rugby union players. The effect of the application of these lifts on mean power output measured using test apparatus that simulated the ruck clean movement featured in rugby union football was examined. The considerably greater increases of the training group on this measure (28% vs 8%) were reflected in greater statistical significance (p<0.01) relative to the improvement for the control group (p<0.05). A significant interaction effect also indicated the training groups responded significantly differently on the test measure following training. A weighted ballistic push up training mode, incorporating a prototype shoulder harness, was investigated in a group of junior academy-level rugby football players. The training group recorded significant improvements in work output measured using a concentric-only push test (p<0.05), whereas countermovement push-up test scores approached significance (P=0.063). The final study employed an overweight ball complex training intervention. Following training the elite academy professional players who served as subjects showed significant improvements (p<0.05) in right-handed and left-handed mean and peak pass velocities.